Hemodynamic Monitoring in Patients With Subarachnoid Hemorrhage: A Systematic Review and Meta-Analysis. Issue 4 (October 2021) - Simonassi, Francesca; Ball, Lorenzo; Badenes, Rafael; Millone, Marco; Citerio, Giuseppe; Zona, Gianluigi; Pelosi, Paolo; Robba, Chiara
Abstract : Aneurysmal subarachnoid hemorrhage (aSAH) often causes cardiopulmonary dysfunction. Therapeutic strategies can be guided by standard (invasive arterial/central venous pressure measurements, fluid balance assessment), and/or advanced (pulse index continuous cardiac output, pulse dye densitometry, pulmonary artery catheterization) hemodynamic monitoring. We conducted a systematic review and meta-analysis of the literature to determine whether standard compared with advanced hemodynamic monitoring can improve patient management and clinical outcomes after aSAH. A literature search was performed for articles published between January 1, 2000 and January 1, 2019. Studies involving aSAH patients admitted to the intensive care unit and subjected to any type of hemodynamic monitoring were included. A total of 14 studies were selected for the qualitative synthesis and 3 randomized controlled trials, comparing standard versus advanced hemodynamic monitoring, for meta-analysis. The incidence of delayed cerebral ischemia was lower in the advanced compared with standard hemodynamic monitoring group (relative risk [RR]=0.71, 95% confidence interval [CI]=0.52-0.99; P =0.044), but there were no differences in neurological outcome (RR=0.83, 95% CI=0.64-1.06; P =0.14), pulmonary edema onset (RR=0.44, 95% CI=0.05-3.92; P =0.46), or fluid intake (mean difference=−169 mL; 95% CI=−1463 to 1126 mL; P =0.8) between the 2 groups. In summary, this systematic review and meta-analysis found only low-quality evidence to support the use of advanced hemodynamic monitoring in selected aSAH patients. Because of the small number and low quality of studies available for inclusion in the review, further studies are required to investigate the impact of standard and advanced hemodynamic monitoring–guided management on aSAH outcomes. Abstract : Supplemental Digital Content is available in the text.